Dilation and shear rheology of mixed beta-casein/surfactant adsorption layers - Kotsmar, Cs; Krägel, J; Kovalchuk, V I; Aksenenko, E V; Fainerman, V B; Miller, R (The journal of physical chemistry. B, 2009)
The present study deals with dilational and shear rheological properties of adsorption layers of the milk protein beta-casein (BCS) mixed with the nonionic dodecyl dimethyl phosphine oxide (C12DMPO) and the positively charged dodecyl trimethyl ammonium bromide (DoTAB), respectively. The drop profile analysis tensiometer PAT-1 was applied for the dilational rheological studies at low frequency harmonic relaxations. A special modification of the setup, consisting of a coaxial capillary combined with a double dosing system, provides exchange of the drop volume during experiments. This arrangement offers a unique protocol for studies of mixed surface layers, formed by sequential adsorption of the individual compounds. The dilational viscoelastic modulus and the dilational viscosity of the mixed layers, built-up in the two different ways, were investigated and compared. The features of the mixed surface layers drawn from the dilational rheology are qualitatively confirmed by the shear rheological parameters measured by torsion shear rheometry ISR-1. Recently derived theoretical models were used for a quantitative description of the equilibrium state and dilational rheology of the surface layers formed by the single components and their mixtures.